Remaining Life and Integrity Assessment of an Atmospheric Storage Tank (T-125) Based on Ultrasonic Testing and API 653 Standard - Khusnun Widiyati; Firza Aliyah (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2025)
This paper presents a Fitness-for-Service (FFS) evaluation and Remaining Life (RL) prediction for the T-125 Atmospheric Storage Tank (AST), which stores Solar (Diesel) fuel at PT. XYZ. The study utilized data from Ultrasonic Testing (UT) conducted over an eight-year inspection interval (2016–2024) to quantify material loss due to corrosion. The analysis was performed strictly according to the guidelines of API Standard 653, 5th Edition. Key parameters, including Corrosion Rate (CR), Minimum Required Thickness (tmin​), and RL, were calculated. While the 1st and 2nd shell courses and the roof plate possess acceptable integrity with RL values ranging from 32.6 to 73.12 years, the 3rd shell course was found to be non-compliant based on the comparison between its calculated minimum required thickness (2.2 mm) and the API minimum plate thickness requirement (2.54 mm). This assessment provides a scientific basis for maintenance planning, emphasizing the need for immediate attention to the 3rd course and continuous monitoring of the 2nd course, which exhibits the highest corrosion rate (0.06 mm/year).